Case Report: Diagnosing Ulcerative Colitis Retrogradely in a Young Indian Male Presenting with Anemia and Thrombocytosis with no Gastrointestinal Symptoms - Fellak, Dr. Naima; Hussein, Dr. Saleh (South Eastern European Journal of Public Health, 2024)
We report a rare case of a young Indian male diagnosed with ulcerative colitis (UC) retrogradely due to the presentation of anemia and thrombocytosis without any initial gastrointestinal (GI) complaints. This case emphasizes the importance of considering inflammatory bowel disease (IBD) in patients with unexplained hematologic abnormalities, even in the absence of GI symptoms.